Implementasi Metode Discovery Learning Berbantuan Alat Peraga Bangun Ruang pada Materi Bangun Ruang SD Kelas VI - Ana Nur Rohima; Imam Tirmidzi; Karina Andarista; Nur Wiji Sholikin (PT Cendekia Education Center, 2026)
This study aimed to determine the effect of implementing the Discovery Learning method assisted by three-dimensional geometric shape teaching aids on the learning outcomes of sixth-grade student in the topic of solid geometry. The study employed a quantitative approach. The research subject consisted of 28 student from SDI Ainur Rahmah, SD Islam Riyadhus Sholihin, and SDN Kedawung 1. The research instruments were pre-test and post-test essay questions used to maasure students' understanding of the elements of solid geometry and the classification of object based on geometric shapes. The data were analyzed using IBM SPSS Statistic through descriptive statistics, Kolmogorov-Smirnov and shapiro-Wilk normality test, and the nonparametic Mann-Whitney test. The results showed that the mean pre-test score of 38.21 increased to 83.61 in the post-test. The normality the results indicated that the data were not normality distributed. Therefore, the analysis was cotinued using Mann-Whitney test. Tha Mann Whitneg test yielyed an Asymp. Sig. (2-tailed) value of 0.000< 0.05, indicating a significant difference between the pre-test and post-test score. The improvement in learning outcomes demonstrates that the Discovery Learning method assisted by solid geometry teaching aids is effective in helping students understand geometric concepts through observation, eksploration, and independent concept discovery activities. Therefore, the Discovery Learning method assisted by solid geometry teaching aids can serve as an effective alternative learning strategy to improve elementary school students' mathematics learning outcomes.